New horizons for vocational lecturers: Spreading the responsibility for transition. A Practice Report - Mark Smith (International Journal of the First Year in Higher Education, 2012)
The transition of students into tertiary study at Unitec has often been seen as the responsibility of learning centres and student services, the domain of ex-language teachers and concerned counsellors, covered by social activities in orientation week and unmentioned for the remainder of the semester. This report describes an initiative to move transition into content areas by widening the horizons of vocational lecturers’ view of what transition involves and indeed of what their discipline encompasses. It introduces a framework summarising some of the “first year experience” literature and discusses the implications it has for lecturers.  The framework is four words – from, with, of, to – which cover the transition into tertiary study and on to graduation.   Designed to be used by academic advisors with vocational lecturers at an Institute of Technology, the framework aims to spread responsibility for transition from support services onto the agendas of departments, programmes and teachers.  It requires teachers to expand their horizons of tertiary education and transition.